2013
DOI: 10.1038/sc.2013.65
|View full text |Cite
|
Sign up to set email alerts
|

Examination and measurement of coping among adolescents with spinal cord injury

Abstract: Study design: Cross-sectional survey. Objectives: To describe coping strategy use in adolescents with spinal cord injury (SCI), to explore the underlying factor structure of a measure of coping among adolescents with SCI and to assess relationships between coping and psychosocial outcomes. Setting: Multiple pediatric SCI centers in the United States. Methods: One hundred and eighty-two participants aged 13-17 years who experienced an SCI completed measures including the Kidcope, Children's Depression Inventory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
1
11
0
1
Order By: Relevance
“…In addition, the participants emphasised that their ability to face challenges evolved and changed over time. On the other hand, they demonstrated that they alternated between strategies when needed, confirming the findings of deRoon-Cassini et al [ 21 ] and studies exploring situational coping [ 41 , 42 ]. Additionally, they described the importance of exerting flexibility.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, the participants emphasised that their ability to face challenges evolved and changed over time. On the other hand, they demonstrated that they alternated between strategies when needed, confirming the findings of deRoon-Cassini et al [ 21 ] and studies exploring situational coping [ 41 , 42 ]. Additionally, they described the importance of exerting flexibility.…”
Section: Discussionsupporting
confidence: 82%
“…Social support increased participation. Youth who reported greater self-efficacy in using coping strategies had more positive psychosocial outcomes [71,89]. Adolescents aged 13-17 years who sustained an SCI report the most effective coping strategies are social support, emotional regulation, and cognitive restructuring.…”
Section: Copingmentioning
confidence: 99%
“…Adolescents aged 13-17 years who sustained an SCI report the most effective coping strategies are social support, emotional regulation, and cognitive restructuring. The use of escape-oriented or avoidant coping was linked to lower psychosocial QOL and heightened symptoms of depression and anxiety [89]. Coping interventions may therefore emphasize training in and harnessing cognitive restructuring and social support while decreasing long-term reliance on escape-oriented coping strategies.…”
Section: Copingmentioning
confidence: 99%
“…A pesar de la falta de consenso existe bastante acuerdo entre los autores en que el afrontamiento activo y centrado en la resolución de problemas está asociado a menores índices de depresión en los primeros momentos en el entorno rehabilitador (3, 15), mientras que el afrontamiento pasivo, que incluye principalmente las estrategias de evitación o centradas en la emoción, suele ir acompañado de un mayor malestar psicológico (7,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). En general, las estrategias de afrontamiento se mantienen más o menos estables a pesar del tiempo que pase desde la lesión (1, 9, 13, 27, 28) y hay evidencia de que el uso de estrategias activas favorece la adaptación y el ajuste social a una LM (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Introductionunclassified